PRELIMINARY ANALYSIS OF WIRELESS COLLABORATIVE NETWORK ON MOBILE DEVICES (Journal of Information and Communication Technology, 2019)
Researchers and companies of telecommunication sector have been working hard to enhance wireless network infrastructure to fulfill the end user’s needs for Internet connectivity. However, it is not easy to satisfy the high demand and expectation of end users always. There are some situations where Internet connectivity is not enabled due to the locations and environmental constraint. For example, network infrastructure breakdown during a disaster or the user’s device is out of the network coverage area. Besides relying only on the network infrastructure provided by telecommunication companies, one possible strategy to provide Internet connectivity in the ubiquitous environment is to exploit the functionality of end-user mobile devices to be the tool to share Internet connectivity. This paper aims to identify the constraints and challenges of forming Wireless Collaborative Network (WCN) by the end user devices. To identify the constraints and challenges, we have reviewed and categorized the past and current research focusing on collaborating mobile devices in the mobile ad-hoc network for communication and resource sharing. For validation, a simple test case was conducted which involves few mobile devices in a random formation. Base on the finding, it is concluded that the biggest challenge of forming WCN is the ability of mobile devices to provide bridging functionality. This paper also discussed the expecting architecture of WCN and suggested the simulation tools with relevant metrics to be considered in this research area.